The Making of Jewish Revolutionaries in the Pale of Settlement - Shtakser, I. author. aut Link
XVII, 222 p.
Keywords: This book examines the emotional aspects of revolutionary experience during a critical turning point in both Russian and Jewish history - the 1905 revolution. Shtakser argues that radicalization involved an emotional transformation, which enabled many young revolutionaries to develop an activist attitude towards reality.